RELATIONSHIP BETWEEN INCIDENCE OF BREAST CARCINOMA AND FIRSTDEGREE RELATIVE POSITIVITY - Ayesha Saeed; Tanya Fareed Khan Khakwani (Baqai Journal of Health Sciences)
Objective: This study aims to find out a relationship between incidence of breast carcinoma & first degree relative positivity.